Variety of Indonesian on Social Media - Ishar, Muh.; Qadrianti, Laeli; Ulfayanti; Harmilawati (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
Language is a communication tool used by the community to interact with great regiliat with a variety of languages. Variety of languages comes from two words, namely variety which means type, kind of, (indicating plural) and language, namely the sound symbol system used to communicate. Then it can be said that the variety of languages is kind, kind, and variations in language usage according to the context of use. The research conducted aims to find out how the variety of Indonesian language use on Twiter's social media, this research is a qualitative descriptive study, this study uses a type of research phenomology with a qualitative approach to the object of humans (human). Data from this study was obtained from a collection of several tweets from the @anyaLalubenar account and @dsuoerboy. The method of data collection in this study is observation and documentation. The results of this study are the discovery of some languages on @dupuperboy and @anyaLalubenar accounts but the variety of languages that are most often used from these two accounts on twiter social media, namely slang and code transfer and mixed code, but also found a variety of foreign languages.